2016
DOI: 10.1186/s12936-016-1108-x
|View full text |Cite
|
Sign up to set email alerts
|

Multi-country comparison of delivery strategies for mass campaigns to achieve universal coverage with insecticide-treated nets: what works best?

Abstract: BackgroundThe use of insecticide-treated nets (ITNs) is widely recognized as one of the main interventions to prevent malaria. High ITN coverage is needed to reduce transmission. Mass distribution campaigns are the fastest way to rapidly scale up ITN coverage. However, the best strategy to distribute ITNs to ensure household coverage targets are met is still under debate. This paper presents results from 14 post-campaign surveys in five African countries to assess whether the campaign strategy used had any eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 21 publications
2
24
2
Order By: Relevance
“…However, among those households reached by either strategy, the net allocation method (which differed by strategy) did not influence whether a household had sufficient LLIN for one per two people. A multi country comparison of LLIN delivery strategies based on 14 surveys from five African countries did not find a significant association between delivery strategy and ownership of a net from the campaign but found a positive association between sleeping space allocation and enough LLIN in the household [28]. …”
Section: Discussionmentioning
confidence: 99%
“…However, among those households reached by either strategy, the net allocation method (which differed by strategy) did not influence whether a household had sufficient LLIN for one per two people. A multi country comparison of LLIN delivery strategies based on 14 surveys from five African countries did not find a significant association between delivery strategy and ownership of a net from the campaign but found a positive association between sleeping space allocation and enough LLIN in the household [28]. …”
Section: Discussionmentioning
confidence: 99%
“…This resulted in a pro-rich gradient especially for the indicator for ‘enough’ ITNs for all household members (concentration index 0.14). Although the inequity was moderate compared to other observations on ITNs or immunization coverage from African countries [ 25 ], it was significant enough to raise concern and in contrast to the high level of equity generally found following mass campaigns [ 3 , 7 ]. Future interventions should establish additional social mobilization targeted especially at this group to ensure they are empowered to request sufficient numbers of ITNs to protect their families keeping in mind, however, that this is likely to further increase cost.…”
Section: Discussionmentioning
confidence: 62%
“…Following the 2007 launch of the new WHO universal coverage strategy for ITNs [ 6 ], campaigns changed from being mostly targeted to young children and pregnant women to mass campaigns for the entire population at risk. From 2008 to 2016 more than one billion ITNs have been delivered to African countries and distributed using a variety of approaches to mass campaign organization which in general were successful in rapidly and equitably scaling up ITN coverage if properly managed and implemented [ 7 ]. A 2015 study analysing factors contributing to declines in malaria morbidity between 2010 and 2015 found that 68% of the 40% reduction in malaria incidence could be attributed to ITNs [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Fixed point distribution was used during the pilot phase, but this approach is not suited to the context of the covid-19 pandemic in terms of compliance with barrier measures. A multi country comparison of ITN delivery strategies based on 14 surveys from ve African countries did not nd a signi cant association between delivery strategy and ownership of a net from the campaign [17][18][19][20][21].…”
Section: Discussionmentioning
confidence: 99%